KONSEP MAJLIS SYURA MENURUT PEMIKIRAN KHAIRUDDIN AL-TUNISI - Syukur, Iskandar (Universitas Islam Negeri Raden Intan Lampung, 2017)
This paper discusses the concept of majlis shura according to Khairuddin's thought. He is a military, bureaucrat, and is well known for his social and political progress in Tunisia and as one of the most important intellectuals in the discourse of contemporary Arab thought. His famous book is Aqwam al-Masalik fi Ma'rifat Ahwal al-Mamalik. The discussion of the concept of majlis shura developed by Khairuddin in this paper refers to that book. Finally, this paper finds thatmajlis shura according to Khairuddin's thought is based on the premise that unlimited power tends to be abused although it is undeniable that there is an absolute ruler doing good for the country and his/her people. In addition, for Khairuddin, unlimited power also can not be used as a reference or rules in the implementation of good governance. Thus, according to Khairuddin the power of government should be limited. The restriction must be done in the way of the division of powers, one of which is by majlis shura. Because one of the authority of this majlis shura is to give attitude and response to all problems of the people as well as possible so that the government's decisions do not contradict the interests of the people, then this majlis shura ought to be based on several principles, among which are freedom, deliberation and balance. Key words: Khairuddin Al-Tunisi, and Majlis Shura